2021
DOI: 10.4018/978-1-7998-6870-5.ch019
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Recognition of Speaker Voice Using a Neural Network-Based Algorithm

Abstract: This chapter explains the speech signal in moving objects depending on the recognition field by retrieving the name of individual voice speech and speaker personality. The adequacy of precisely distinguishing a speaker is centred exclusively on vocal features, as voice contact with machines is getting more pervasive in errands like phone, banking exchanges, and the change of information from discourse data sets. This audit shows the location of text-subordinate speakers, which distinguishes a solitary speaker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Face expressions throughout civilizations are examined in this article. Three methodologies are used to analyse emotional facial reactions: sociological, physiological and computerized Presentations from world-renowned experts in behavioural, physiological, and mathematical disciplines are included [26].…”
Section: Literature Surveymentioning
confidence: 99%
“…Face expressions throughout civilizations are examined in this article. Three methodologies are used to analyse emotional facial reactions: sociological, physiological and computerized Presentations from world-renowned experts in behavioural, physiological, and mathematical disciplines are included [26].…”
Section: Literature Surveymentioning
confidence: 99%
“…The supplied image's grayscale power remains between 80 and 250 dots per inch. Essential characteristics, including image contrast, Aspect Ratio-AR, resolution, & brightness, were supplied in stealth mode [23]. Adaptive histogram equalization is a process to extract edge-level features from an input image.…”
Section: Brain Mri Image Enhancementmentioning
confidence: 99%
“…The following work concluded that regression classification is used to predict HD more accurately than other techniques by Saikumar and Rajesh, 2020a,b. R-C4.5 is proposed, and its features are extractí from the given technique by Koppula et al (2021). The study used their equipment and found it a very beneficial machine in the healthcare industry for predicting MLbased approaches Garigipati et al (2022).…”
Section: Related Workmentioning
confidence: 99%